A review on fundamental principles of a natural gas hydrate formation prediction - Abbasi, A. (Taylor and Francis Ltd., 2022)
The hydrocarbons components are formed in multiple phase flow of gasses in a variation of temperature, pressure and composition, which results in flow change for hydrocarbon fluid. The presence of solids can cause severe problems in oil and gas production and transmission systems. Among them, the frequently occurring solid precipitation problems are due to hydrate formation which is thoroughly studied in this research. Hydrates provide a significant risk for all high-pressure natural gas transmissions, including connecting lines and manifold systems in oceanic transportation of compressed natural gas. Better safety and reliability conditions are very important in high-pressure natural gas transportation systems to properly analyze hydrate issues in the pipeline. The pressure and temperature variations of a system are one of the major causes which may lead to hydrate formation in hydrocarbon transmission. Fluid flow through different channels, equipment, production tubing and transmission pipeline were producing unstable temperature and pressure in hydrocarbon production and exploration system may cause the formation of a hydrate. Â© 2022 Taylor & Francis Group, LLC.